Fraxin inhibits melanogenesis by suppressing the ERK/MAPK pathway and antagonizes oxidative stress by activating the NRF2 pathway - Liping Luo; Xing Yu; Hongliang Zeng; Yibo Hu; Ling Jiang; Jinhua Huang; Chuhan Fu; Jing Chen; Qinghai Zeng (Heliyon, 2023)
Hyperpigmentation disorders, such as melasma and freckles, are highly prevalent and draw increasing attention. Patients thus tend to seek effective and safe cosmetic whitening agents. Fraxin, a bioactive substance extracted from Cortex Fraxini, possesses anti-inflammation and antioxidant properties. In this study, we further explored the anti-melanogenic activities of fraxin were explored in vitro and in vivo. We found that pretreatment with fraxin decreased the melanin content of MNT1 cells and zebrafishes. In MNT1 cells, melanogenesis-related proteins, such as MITF, TYR, TYRP1, and DCT were down-regulated and tyrosinase activity was reduced under fraxin treatment. Further exploration of the mechanism revealed that fraxin could inhibit the phosphorylation of ERK, which is closely related to melanogenesis. Besides, fraxin also protected MNT1 cells from H2O2-induced apoptosis via scavenging reactive oxygen species (ROS) in cells. Further experimentation revealed that fraxin could activate NRF2 and upregulate antioxidase CAT and HO-1. In conclusion, fraxin could be an effective agent with anti-melanogenesis and antioxidant properties for hyperpigmentation disorders.